2017
DOI: 10.1093/nar/gkx163
|View full text |Cite
|
Sign up to set email alerts
|

ICF-specific DNMT3B dysfunction interferes with intragenic regulation of mRNA transcription and alternative splicing

Abstract: Hypomorphic mutations in DNA-methyltransferase DNMT3B cause majority of the rare disorder Immunodeficiency, Centromere instability and Facial anomalies syndrome cases (ICF1). By unspecified mechanisms, mutant-DNMT3B interferes with lymphoid-specific pathways resulting in immune response defects. Interestingly, recent findings report that DNMT3B shapes intragenic CpG-methylation of highly-transcribed genes. However, how the DNMT3B-dependent epigenetic network modulates transcription and whether ICF1-specific mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 84 publications
4
64
0
Order By: Relevance
“…DNA methylation comparison between L-Pro treated-and Tet TKO mESCs was performed as described (17). Briefly, the Tet TKO hyper-DMRs (18) in which at least 3 CpGs were covered by L-Pro RRBS experiments (6) were selected for the analysis.…”
Section: Dna Methylation Data Analysismentioning
confidence: 99%
“…DNA methylation comparison between L-Pro treated-and Tet TKO mESCs was performed as described (17). Briefly, the Tet TKO hyper-DMRs (18) in which at least 3 CpGs were covered by L-Pro RRBS experiments (6) were selected for the analysis.…”
Section: Dna Methylation Data Analysismentioning
confidence: 99%
“…It is well known that both during immune cell differentiation and B or T cell activation, DNA methylation combined with the transcription factors play a vital role in the regulation of gene expression (78), which through DNA methylation of cytosines in the context of cytosineguanine dinucleotides (CpG), often located in clusters (CpG islands) within regulatory regions such as promoters and enhancers. Epigenetics is also thought to be essential for V(D)J rearrangement, and immunological memory (79,80) and recent studies have identified DNA methylation alterations in common variable immunodeficiency (CVID) (78), the Immunodeficiency, Centromere instability and Facial anomalies (ICF) (81,82) and ATM deficiency (83).…”
Section: Epigeneticsmentioning
confidence: 99%
“…Indeed, the aberrant hypomethylation at alternative or cryptic TSSs caused by DNMT3B dysfunction leads to their illegitimate activation interfering with the transcription and elongation of the appropriate mRNA. Switching to an alternative intragenic TSS may be caused by the hypermethylation of the canonical TSS following an altered recruitment of DNMT3A/3B proteins (Figure 1A ; Gatto et al, 2017 ).…”
Section: Traditional and Novel Functions Of Dnmt3b In Dna Methylationmentioning
confidence: 99%